Paper Assignment on Moneyball - Caronna, C. (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
Demonstrate how Thompson’s levels model applies to the Oakland A’s as depicted in Moneyball. In this demonstration you need to (1) describe which members of the organization belong to which level of the organization; and (2) provide evidence from Moneyball that demonstrates how each relevant theoretical perspective applies to each level, as specified by Thompson’s levels model (theoretical perspectives should be at least the broad, such as "rational," "natural," "open," and potentially the more specific, such as scientific management, bureaucracy, bounded rationality, cooptation, institutionalization, etc.).